The Prevalence of Radiographic Findings of Structural Hip Deformities in Female Collegiate Athletes. (June 2015) - Kapron, Ashley L.; Peters, Christopher L.; Aoki, Stephen K.; Beckmann, James T.; Erickson, Jill A.; Anderson, Mike B.; Pelt, Christopher E.
Background: Structural deformities of the hip, including femoroacetabular impingement (FAI) and acetabular dysplasia, often limit athletic activity. Previous studies have reported an increased prevalence of radiographic cam FAI in male athletes, but data on the prevalence of structural hip deformities in female athletes are lacking. Purpose: (1) To quantify the prevalence of radiographic FAI deformities and acetabular dysplasia in female collegiate athletes from 3 sports: volleyball, soccer, and track and field. (2) To identify possible relationships between radiographic measures of hip morphologic characteristics and physical examination findings. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Anteroposterior (AP) pelvis and frog-leg lateral radiographs were obtained from 63 female athletes participating in Division I collegiate volleyball, soccer, and track and field. Lateral center edge angle (LCEA) and acetabular index were measured on AP films. Alpha angle and head-neck offset were measured on frog-leg lateral films. Pain during the supine impingement examination and hip rotation at 90° of flexion were recorded. Random-effects linear regression was used for group comparisons and correlation analyses to account for the lack of independence of observations made on left and right hips. Results: Radiographic cam deformity (alpha angle >50° and/or head-neck offset <8 mm) was found in 48% (61/126) of hips. Radiographic pincer deformity (LCEA >40°) was noted in only 1% (1/126) of hips. No hips had radiographic mixed FAI (at least 1 of the 2 cam criteria and LCEA >40°). Twenty-one percent (26/126) of hips had an LCEA <20°, indicative of acetabular dysplasia, and an additional 46% (58/126) of hips had borderline dysplasia (LCEA ≥20° and ≤25°). Track and field athletes had significantly increased alpha angles (48.2° ± 7.1°) compared with the soccer players (40.0° ± 6.8°; P < .001) and volleyball players (39.1° ± 5.9°; P < .001). There was no significant difference in the LCEA (all P > .914) or the prevalence of dysplasia (LCEA <20°) between teams (all P > .551). There were no significant correlations between the radiographic measures and internal rotation (all P > .077). There were no significant differences (all P > .089) in radiographic measures between hips that were painful (n = 26) during the impingement examination and those that were not. Conclusion: These female athletes had a lower prevalence of radiographic FAI deformities compared with previously reported values for male athletes and a higher prevalence of acetabular dysplasia than reported for women in previous studies.